Emotions d’élus et découpage territorial. Recompositions intercommunales dans l’aire urbaine havraise - Lilian Loubet (L'Espace Politique)
Territorial restructuring appears to be a product of “rational” variables (technical, political and territorial), but also of “irrational” ones. The emotions of elected officials also partially condition the construction of territories and the redrawing of their boundaries. Drawing on a series of interviews with mayors, analysis of the way in which their emotions affect their decisions is made, and the territorial restructuring that ensues. In the national context of a France affected by institutional change (the new phase of decentralisation), the urban area of Le Havre (Normandie) illustrates the issues of restructuring that occur in many territories. The project of an amalgamation of three inter-municipalities to create a larger entity helps to provide input into the works of the local geopolitics. In addition to the significance of the boundary and the project, a majority of elected officials from one of the inter-municipalities sees it as being a forced absorption (backed by the former mayor of Le Havre, today the Prime Minister of France). Discussions about the questions of territoriality, identity (urban versus rural), and of sovereignty take place in a context where the affective dimension plays a significant role. Consequently, the literature from the fields of “emotional geography”, “political geography”, “cognitive analysis of public policies” and “territorial development” constitute the theoretical framework of this article. The cognitive sciences are also brought into play in order to analyse the cognitive structure of mayoral emotions. Every mayor of the inter-municipality who “joined the resistance” took part in semi-directive interviews carried out in the city hall on condition of anonymity. The data collected were the object of a contents analysis, a comparative analysis and a textual statistical analysis. We were able to determine from the Le Havre case that the more an elected official benefits from cognitive competences and resources in the framework of his “job as mayor” (high level of instruction, strong leadership and expertise), the less permeable he seems to be to the emotions inherent in territorial play. These could have a lesser influence on his decisions and he might be prone to a form of “pragmatism”. Conversely, those elected officials having few resources at their disposal will be more inclined to allow their emotions to affect the restructuring in question. If, according to our findings, this correlation appears significant, our analysis is more than an interdependence and it is not a matter of opposing competences and emotions. The essential point of our article lies elsewhere. Spatial restructuring combines political, cognitive, territorial and emotional dimensions. Furthermore, isolating the latter variable would lead to a loss of its heuristic potential. Both the cause and consequence, the emotions experienced by mayors are active principles, but also indicative of territorial play. Studying the redrawing of space through the prism of emotions makes it possible to shed light on the decision-making processes at work, the mechanisms of governance activated and the geopolitics that ensue. The emotions are an enhancing substance, intensifying the questions of power, identity and sovereignty, etc. In that, they constitute a springboard for action and a move from word to deed.